Effectiveness of jacobson progressive relaxation technique and deep breathing exercises on quality of life in prolonged hospitalized patients - Deshpande, Pranav; Poonam Patil, (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2024)
Background: Middle age is a crucial period of life during which mental health related problems may become a cause or an effect of various physical health problems among which anxiety, psychological distress and sleep difficulties are commonly observed .The prevalence rate for sleep disturbance in hospitalized adults is 40% to 50%.Barriers to proper sleep in hospitalized older patients are environmental factors like noise, light disruption and medical care related factors like early morning vital signs, phlebotomy and patient factors like pain. Jacobson progressive muscle relaxation and deep breathing exercises are the techniques that can increase the quality of sleep in prolonged hospitalized patients. As the association of anxiety disorders are moderately associated with reduced quality of sleep which results in reduced quality of life .Recently studies revealed significant association between higher anxiety, depression and poor sleep quality in chronically ill hospitalized older patients .Poor sleep results in increased risk of in significant morbidity and mortality. Complications of poor quality of sleep are Parkinson’s disease, Alzheimer’s disease, arthritis pain ,cardiovascular disease or any neurological condition. Methods: The study consisted of prolonged hospitalized patients and sample size was selected on the basis of inclusion and exclusion criteria.30 participants were included in this study with sample size 30. APA sleep disturbance scale and geriatric anxiety inventory scale was used to collect the data.Results: Out of total 30 subjects, there was significant difference between the pre intervention score of Group A which was 294±67.38 and Group B which was 262±72.32 and post intervention score of Group A which was 321±63.90 and Group B which was 523±66.72 in the Quality of sleep in which p value was 0.0001 and t value was  5.344 in Group A and 13.116 in Group B which was extremely significant in the subjects who received Jacobson progressive relaxation technique and deep breathing exercises.The pre intervention score Group A was 1.46±0.516 and Group B was 1.34±0.442 and the post intervention score of Group A was 2.16±0.459 and Group B was 3.77±0.502 in the Anxiety in which p value was 0.0001 and t value of Group A  was 6.808 and Group B was 16.205 which was extremely significant in the subjects who received Jacobson progressive relaxation technique and deep breathing exercises.Conclusion: The significant reduction in the anxiety and improvement in the quality of sleep and life showed that Jacobson progressive muscle relaxation technique and deep breathing exercises are effective. How to cite this article:Deshpande P, Patil P. Effectiveness of JacobsonProgressive Muscle Relaxation and DeepBreathing Exercises on Quality of Life inProlonged Hospitalised Patients. J Adv ResPsychol Psychother. 2023;6(3&4):1-5.